Deficit or Credit? A Comparative, Qualitative Study of Gender Agency and Female Gang Membership in Los Angeles and Glasgow. (July 2020) - Deuchar, Ross; Harding, Simon; McLean, Robert; Densley, James A.
To date, there has been a paucity of comparative, qualitative research exploring the nuances of women's gang involvement beyond the United States. In this article, we seek to address this gap by drawing upon qualitative interviews with small samples of self-nominated female gang members in Los Angeles, California (United States) and Glasgow, Scotland (United Kingdom). The emerging insights indicated that two key models of entry into the "social field" of the gang emerged in the data: a deficit model entry linked to drugs and debt and a credit model of entry where women were considered to bring social skill, expertise, and agency into the gang. Implications in terms of testable hypotheses for future research as well as for future practice are outlined.